A Review of Incidental L2 Vocabulary Learning of English - Zhong, Chuhan (International Journal of Social Sciences and Public Administration, 2024)
This article discusses the importance of incidental vocabulary learning in English language acquisition. Incidental learning is an effective method for acquiring new words and phrases naturally through exposure to language input. The article emphasizes the role of incidental learning in increasing vocabulary knowledge and language understanding, and explores its pedagogical implications in language teaching.